Hold the Salt: History of Salt Restriction as a First-line Therapy for Menière's Disease. Issue 6 (July 2020) - Shim, Timothy; Strum, David Poran; Mudry, Albert; Monfared, Ashkan
Abstract : Objectives: To determine the historical origins of the usage of the salt restriction diet as an intervention for Menière's disease (MD). Methods: Articles on MD and salt restriction were identified using Pubmed and Google scholar. Original manuscripts from 19th and 20th century as well as selected otological textbooks in English, German, and French were also reviewed. Results: The oldest recommendation of salt restriction in the literature was by Dederding (1889–1955) in 1929. She and her mentor, Sydney Holger Mygind (1884–1970), believed MD was caused by dysfunctional water metabolism. In several published manuscripts, they proposed that a reduced salt and fluid diet was an effective treatment for MD. Their contemporaries supported their findings, most notably, Albert C. Furstenberg (1890–1969) who suggested salt restriction alone as treatment for MD. Furstenberg, in his initial study implementing salt restriction in 15 patients with MD and then in a larger study with 150 patients, was the first to produce results that supported salt restriction as therapy for MD. It was not until 1980, when LB Jongkees first published his criticism of this treatment, that salt restriction was questioned. Since then, numerous published articles have been critical of salt restriction therapy and skeptical of its initial adoption into clinical practice. Conclusions: Since Dederding's and Mygind's publications in 1929 and Furstenberg's trial in 1934, the salt restriction diet has remained a primary first-line treatment for MD. Since the 1950s, various publications have both supported and argued this treatment, and the evidence of its validity remains inconclusive.